Molecular mechanisms of predation of planktonic protist Hemistasia phaeocysticola - Knobloch, Tomáš (Jihočeská univerzita, 2021)
In this thesis growth curves under specific conditions, fluorescence microscopy, and transcriptomic analyses were used to investigate whether the marine protist Hemistasia phaeocysticola is able to prey on bacteria and the determination of its molecular mechanisms of predation.
Molecular mechanisms of predation of planktonic protist Hemistasia phaeocysticola
Keywords: protist; diplonemids; bacteriovory; protist; diplonemids; bacteriovory